2010
DOI: 10.1590/s0037-86822010000600033
|View full text |Cite
|
Sign up to set email alerts
|

Subdoses of primaquine in overweight patients and malaria vivax relapses: report of two cases in the Federal District, Brazil

Abstract: Two cases of malaria by Plasmodium vivax relapsed after treatment with drugs in doses recommended by the Ministry of Health are presented. Both patients were overweight and were followed in the Federal District, an area considered free from vector transmission of the disease. Radical cure was obtained after medication with the same drugs in weight proportional doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…These results agree with studies that suggested dosing adjustments for patients weighting over 70 kg at a time when obesity was not yet a global problem [37-40]. …”
Section: Discussionsupporting
confidence: 90%
“…These results agree with studies that suggested dosing adjustments for patients weighting over 70 kg at a time when obesity was not yet a global problem [37-40]. …”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there have been multiple reports of treatment failure from various parts of the world where the older regimen of primaquine had been administered, although some of these may be due to poor compliance (data from Korean peninsula, Afghanistan, India, Vietnam, Thailand) [18-21]. Still, it had been shown that for individuals with a higher bodyweight (> 70 kg), a 15 mg/d primaquine dose was ineffective in preventing relapses even with good compliance [1,22]. Therefore the current recommendation of the Center for Disease Control (CDC), USA for use of primaquine for radical cure stands at 0.5 mg/kg/d for 14 days (maximum of 30 mg/d) [1].…”
Section: Methodsmentioning
confidence: 99%
“…A review of treatment failure with primaquine containing regimens in different endemic areas have shown that while adding primaquine to a blood schizontocidal agent considerably reduced the rate of relapse, the protective effect was more with a higher total dose of primaquine as well as a higher dose per body weight [59]. In some instances of reported failure with primaquine, inadequate dosing compared to body weight of individuals was obvious [22,59,60]. It also questions the validity of earlier case reports of treatment failure with primaquine containing regimens of 15 mg/d (or less than 0.5 mg/kg/d) over 14 days [61-66].…”
Section: Methodsmentioning
confidence: 99%
“…En algunas zonas endémicas, la malaria coexiste con una alta prevalencia de deficiencia de glucosa 6 fosfato deshidrogenasa (d-G6PD) (5, 6), lo que condiciona el empleo generalizado de la primaquina sin previa evaluación de la existencia de d-G6PD (7). El no uso de la primaquina o su empleo en dosis subterapéuticas facilitan la recaída de P. vivax a partir de los hipnozoítos (8)(9)(10).…”
Section: Introductionunclassified